Creatività e progettualità alla prova dell’estetica - Mazzocut-Mis, Maddalena; Scanziani, Andrea (Aesthetica Preprint, 2023)
Creativity and innovation are common terms used as synonyms in political, economic, and scientific contexts. However, a certain field-specific interpretation of creativity is required when the European research and innovation programs for science and creative sectors are considered. Creativity is interpreted by aesthetics in relation to artistic production, play, and imagination. The paper considers the European policy for creative projects to show the common features of creativity as recognized by aesthetics.